(3GdeOhfIs - (3CHh YHO Gddg YHO GdQMef GHf GdbGSe GdeGdcj,J (B191 (3g` s
(3ChdgG (B:s
(3HHGH aj ESJHQGA GdCeI GdeSJMGVI s
(3BNQgG (B:s
(3Je cJGH GdCbVjI HMeO Gddg hYhfg hjdjg cJGH GdTgGOGJ ef GdeOhfI QhGjI SMfhf s
(3HjhY hCbVjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1644s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs